Effects of Curcumin on Tobacco Smoke‐induced Hepatic MAPK Pathway Activation and Epithelial–Mesenchymal Transition In Vivo. (6th June 2017) - Liang, Zhaofeng; Wu, Rui; Xie, Wei; Xie, Chunfeng; Wu, Jieshu; Geng, Shanshan; Li, Xiaoting; Zhu, Mingming; Zhu, Weiwei; Zhu, Jianyun; Huang, Cong; Ma, Xiao; et al.
Abstract : Tobacco smoke is a major risk factor for hepatic cancer. Epithelial–mesenchymal transition (EMT) induced by tobacco smoke is crucially involved in the initiation and development of cancer. Mitogen‐activated protein kinase (MAPK) pathways play important roles in tobacco smoke‐associated carcinogenesis including EMT process. The chemopreventive effect of curcumin supplementation against cancers has been reported. In this study, we investigated the effects of tobacco smoke on MAPK pathway activation and EMT alterations, and then the preventive effect of curcumin was examined in the liver of BALB/c mice. Our results indicated that exposure of mice to tobacco smoke for 12 weeks led to activation of ERK1/2, JNK, p38 and ERK5 pathways as well as activator protein‐1 (AP‐1) proteins in liver tissue. Exposure of mice to tobacco smoke reduced the hepatic mRNA and protein expression of the epithelial markers, while the hepatic mRNA and protein levels of the mesenchymal markers were increased. Treatment of curcumin effectively attenuated tobacco smoke‐induced activation of ERK1/2 and JNK MAPK pathways, AP‐1 proteins and EMT alterations in the mice liver. Our data suggested the protective effect of curcumin in tobacco smoke‐triggered MAPK pathway activation and EMT in the liver of BALB/c mice, thus providing new insights into the chemoprevention of tobacco smoke‐associated hepatic cancer. Copyright © 2017 John Wiley & Sons, Ltd.